"Overcome your anger if you are a man": Silencing women's agency to voice violence against women. (July 2016) - Akyüz, Selin; Sayan-Cengiz, Feyda
Synopsis: This study traces the relation between male violence and masculinist norms that attribute political agency exclusively to men. Through critical analysis of a recent campaign initiated as an effort to fight violence against women in Turkey by addressing men as the only agents endowed with agency to solve the problem, we explore the ways in which this discourse risks marginalizing women who seek empowerment through women's solidarity. We uncover three patterns: (1) the assumption of a "cultural particularity" in Turkey nested in the traditional family structure which should allegedly be left unquestioned; (2) glorification of values attributed to the masculine; (3) taking violence as an individual problem of "anger management." We argue that this campaign is inimical to the aim it declares because by marginalizing feminist efforts to question the social and structural patterns of male violence, it deprives women of political agency essential in the struggle against this problem. Highlights: The article traces the relation between male violence and the masculinist norms that attribute political agency exclusively to men. The article analyzes a campaign initiated as an effort to battle violence against women in Turkey The article uncovers that the campaign discourse praises traditional family and takes male violence as an individual problem. We argue that by taking men as the only agents to solve male violence issue, the campaign deprives women of political agency